1971
DOI: 10.1038/bjc.1971.42
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Induced Host Anaemia on the Viability and Radiosensitivity of Murine Malignant Cells in vivo

Abstract: SUMMARY.-Within 48 hours of the institution of severe phenylhydrazineinduced anaemia in mice bearing ascites tumours or generalised leukaemia, a substantial proportion of the malignant cells disappeared respectively from the peritoneal cavity or infiltrated liver. The results of radiobiological experiments permitting determination of the proportion of viable leukaemia cells which were severely hypoxic and relatively radioresistant in the livers of leukaemic mice, showed that induction of anaemia was associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Hewitt and Blake (1971) looked at the effect of inducing anaemia with phenylhydrazine and then correcting it by blood transfusion before irradiation. This procedure gave clear radiosensitization in one tumour, a leukaemia cell line but minimal effect in another, a sarcoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hewitt and Blake (1971) looked at the effect of inducing anaemia with phenylhydrazine and then correcting it by blood transfusion before irradiation. This procedure gave clear radiosensitization in one tumour, a leukaemia cell line but minimal effect in another, a sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that preconditioning to anaemia (Hirst, 1986;Hirst & Wood, 1987) permits several tumours to be sensitized by blood transfusion but that the sensitization is transient, the effect being lost in 6-48 h depending on tumour line. This adaptation phenomenon could account for the inability of Hewitt and Blake (1971) to sensitize one of their tumours (Sarcoma F), because they permitted an interval of up to 20h to elapse between transfusion and irradiation. It also leads us to suspect that the sensitization we have achieved with the transfusion of low affinity blood will be transient.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor hypoxia results in relative irradiation and chemotherapy resistance. [4][5][6][7] In addition, hypoxia is an important stimulus for angiogenesis; it drives the process of malignant progression resulting in the up regulation of enzymes and proteins which lead to tumor invasion, the down regulation of cell surface antigens resulting in cell detachment, genomic instability with mutagenic properties and the increased clonal selection of cells with apoptosis enhanced survival. 8 It has been assumed that low hemoglobin levels may therefore result in impaired tumor oxygenation, although tumors exposed to low levels of oxygen as seen in the chronic anemia of malignancy are able to adapt to the microenvironment and restore tumor oxygenation.…”
Section: Introductionmentioning
confidence: 99%
“…The number of clonogenic cells after a single X-ray dose of 20Gy was slightly lower (P<0.05) in the anaemic animals (2.3 x I04g-') than in controls (5.2 x I04g-') though there was no significant difference in the surviving fractions. Mice bearing KHT tumours became anaemic with haematocrits falling to 65% of normal as their tumours grew from 300-1200 mg. A second 'test' tumour was implanted one week after the first 'anaemia-inducing' tumour so that estimates of radiosensitivity could all be carried out on tumours within the same size range (150-300mg (Bush, 1986;Dische, 1990;Hirst, 1986;Overgaard et al, 1989) though not every study supports this view (Fazekas et al, 1989) (Hirst & Wood, 1987) administration of phenylhydrazine (Hewitt & Blake, 1971;Siemann et al, 1989;Tanaka et al, 1969) low iron diets (McCormack et al, 1990;Walker et al, in press) the effects of growth of some tumours (Hill et al, 1971) and kidney irradiation (Rojas et al, 1987). The results of these studies will be considered later, but it is at once obvious that several inconsistencies exist and that the induction of anaemia probably brings into effect adaptive mechanisms that have a profound influence on tumour radiosensitivity.…”
mentioning
confidence: 99%